Differential antagonism of tetramethylenedisulfotetramine-induced seizures by agents acting at NMDA and GABA(A) receptors - Shakarjian, Michael P. (2012)
Tetramethylenedisulfotetramine (TMDT) is a highly lethal neuroactive rodenticide responsible for many accidental and intentional poisonings in mainland China. Ease of synthesis, water solubility, potency, and difficulty to treat make TMDT a potential weapon for terrorist activity. We characterized TMDT-induced convulsions and mortality in male C57BL/6 mice. TMDT (ip) produced a continuum of twitches, clonic, and tonic-clonic seizures decreasing in onset latency and increasing in severity with increasing dose; 0.4 mg/kg was 100% lethal. The NMDA antagonist, ketamine (35 mg/kg) injected ip immediately after the first TMDT-induced seizure, did not change number of tonic-clonic seizures or lethality, but increased the number of clonic seizures. Doubling the ketamine dose decreased tonic-clonic seizures and eliminated lethality through a 60 min observation period. Treating mice with another NMDA antagonist, MK-801, 0.5 or 1 mg/kg ip, showed similar effects as low and high doses of ketamine, respectively, and prevented lethality, converting status epilepticus EEG activity to isolated interictal discharges. Treatment with these agents 15 min prior to TMDT administration did not increase their effectiveness. Post-treatment with the GABA(A) receptor allosteric enhancer diazepam (5 mg/kg) greatly reduced seizure manifestations and prevented lethality 60 min post-TMDT, but ictal events were evident in EEG recordings and, hours post-treatment, mice experienced status epilepticus and died. Thus, TMDT is a highly potent and lethal convulsant for which single-dose benzodiazepine treatment is inadequate in managing electrographic seizures or lethality. Repeated benzodiazepine dosing or combined application of benzodiazepines and NMDA receptor antagonists are more likely to be effective in treating TMDT poisoning.